Evaluation of the Quality of Semen and Sexual Function in Men with Inflammatory Bowel Disease. Issue 7 (16th May 2017) - Valer, Paz; Algaba, Alicia; Santos, Daniel; Fuentes, Manuel E; Nieto, Elva; Gisbert, Javier P; López, Pilar; Quintanilla, Elvira; García-Alonso, Francisco J; Guerra, Iván; Páez, Álvaro; Bermejo, Fernando
Abstract: Background: Data on fertility rates and medication safety in men with inflammatory bowel disease (IBD) are limited. The aim of this study was to evaluate whether there is a seminal alteration in patients with IBD and, if so, to evaluate the mechanisms that may play a role according to what has been described in the literature. Its secondary aim was to evaluate the impact on male sexual function of IBD. Methods: Multicenter, cross-sectional, case series study comparing men with IBD and control subjects. Semen analysis was performed according to the recommendations of World Health Organization. The impact on male sexual function was evaluated with the International Index of Erectile Function questionnaire. Results: On multivariate analysis, patients with Crohn's disease had lower sperm concentrations compared with those with ulcerative colitis (median [interquartile range], 34.5 [19.2–48] versus 70 [34.5–127.5], P = 0.02) and lower seminal zinc levels (mean ± SD, 1475 ± 235 μmol/L versus 2221 ± 1123 μmol/L, P = 0.04). Patients with Crohn's disease on anti–tumor necrosis factor treatment had better progressive motility (mean ± SD, 56.7 ± 17.7 versus 35.1 ± 22.1, P = 0.01) and sperm morphology (14.4 ± 7.1 versus 7.6 ± 4.9, P = 0.04) than those who were not on anti–tumor necrosis factor. Regarding sexual function, no significant differences were found across patients with IBD and control subjects. Conclusions: Men with Crohn's disease showed a trend toward poorer semen quality than those with ulcerative colitis. Treatment with anti–tumor necrosis factor drugs does not seem to be associated with poor sperm quality. In patients in clinical remission, male sexual function is not affected by IBD.